Gestión administrativa en la empresa lavandería y tintorería al paso en la ciudad de Machala. - Aguilar Valladolid, Katty Viviana; Nuñez Ramon, Lady Franchesca (Machala : Universidad Técnica de Machala, 2024)
The objective of this project is to analyze the effect of the administrative management within the decision making for greater feasibility of the company, through the descriptive type research and case study with descriptive, explanatory and exploratory levels of research, the following work is developed through the qualitative and deductive-inductive methodology, for the application of information collection instruments were used: interview and observation sheet, which allowed to collect relevant information on administrative management. The development of the same allows identifying the problem of how administrative management influences the growth of Al Paso Laundry and Dry Cleaning in the city of Machala, due to the fact that within this microenterprise there is no knowledge in the area of administrative management, identifying the internal and external factors that intervene in the development and sustainability of the company. The administrative management in the company Lavandería Y Tintorería Al Paso in Machala involves a series of key processes to ensure the efficiency and quality of services. From the reception and classification of garments to the final delivery, various resources must be coordinated to meet the needs of customers in a timely and effective manner.
El presente proyecto tiene como objetivo analizar el efecto de la gestión administrativa dentro de la toma de decisiones para mayor factibilidad de la empresa, mediante las investigación de tipo descriptiva y estudio de caso con niveles de investigación descriptivo, explicativo y exploratorio, el siguiente trabajo se desarrolla mediante la metodología cualitativo y deductivo-inductivo, para la aplicación de instrumentos de recolección de información se utilizó: entrevista y la ficha de observación, lo que permitió recopilar información relevante sobre la gestión administrativa. El desarrollo del mismo permite identificar la problemática de ¿Cómo el manejo administrativo influye en el crecimiento de la Lavandería y Tintorería Al Paso en la ciudad de Machala? debido a que dentro de esta microempresa no cuenta con conocimientos en el área de gestión administrativa, identificando los factores internos y externos que intervienen en el desarrollo y sostenibilidad de la empresa.La gestión administrativa en la empresa Lavandería Y Tintorería Al Paso en Machala implica una serie de procesos clave para garantizar la eficiencia y la calidad en los servicios. Desde la recepción y clasificación de prendas hasta la entrega final, se deben coordinar diversos recursos para satisfacer las necesidades de los clientes de manera oportuna y efectiva.
Keywords: GESTION ADMINISTRATIVA; PROCESO ADMINISTRATIVO; INVENTARIOS; SISTEMA CONTABLE